Healthcare performance of leprosy management in peripheral health facilities of Dhanusa and Mahottari, Nepal - Ram Kumar Mahato; Uttam Ghimire; Bijay Bajracharya; Binod K. C.; Deepak Bam; Deepak Ghimire; Uttam Raj Pyakurel; David T. S. Hayman; Basu Dev Pandey; Chuman Lal Das; Krishna Prasad Paudel (BMC Health Services Research)
Abstract Background The global elimination of leprosy transmission by 2030 is a World Health Organization (WHO) target. Nepal’s leprosy elimination program depends on early case diagnosis and the performance of health workers and facilities. The knowledge and skills of paramedical staff (Leprosy Focal Person, LFP) and case documentation and management by health facilities are therefore key to the performance of health care services. Methods The performance of health workers and facilities was evaluated through a combined cross-sectional and retrospective study approach of 31 health facilities and their LFPs in Dhanusa and Mahottari Districts in Madhesh Province, Nepal. An average of 6 patients (paucibacillary, PB, or multibacillary, MB) per health facility registered within the 2018/2019 fiscal year were also enrolled in the study. LFP knowledge (e.g., of the three cardinal signs) and skills (e.g., nerve palpation) and facility processes (e.g., record keeping) were scored (e.g., 0, 1) and then rescaled to a proportion, where 1 is perfect. Internal benchmarking was used to guide performance management. Results Overall LFP knowledge and skill scores of health workers ranged from 0.16 to 0.63 (median 0.53, 95% confidence interval (CI), 0.46–0.6). Case documentation scores ranged from 0.15 to 0.87 (median 0.37, 95% CI 0.36–0.38), case management scores from 0.38 to 0.79 (median 0.54, 95% CI 0.53–0.55) and overall healthcare scores from 0.36–0.62 (median 0.48, 95% CI 0.47–0.49). Leprosy-related training was significantly related to the knowledge and skills of the health workers. All identified cases (n = 187) adhered to the complete treatment and release after treatment (RFT) scheme, out of which 84.5% were satisfied with the service they were provided. Leprosy disability and ear hand and feet (EHF) scores were not significantly reduced in treated patients during the study period, but counseling by LFPs significantly improved cases’ positive beliefs and practices regarding self-care. Conclusion Overall leprosy care median performance was low (53%) and can be improved by evidenced-based training, onsite coaching, monitoring, and supervision to facilitate leprosy transmission elimination. The results highlight many of the challenges facing leprosy elimination programs.